Storm prey [large type] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Prey novel., 2010)
Weather Karkinnen, surgeon, wife of an investigator named Lucas Davenport, unwittingly witnesses the robbery of the hospital pharmacy where she works. With the death of a pharmacy worker on their hands, the three thieves set out to find out who Weather is, and eliminate the only possible witness.